Mnohocetné extrarenální komplikace Wegenerovy granulomatózy - Ríhová, Z; Merta, M; Rysavá, R; Bezdícek, P; Danzig, V; Gorican, K; Lukás, J; Skalická, P; Vernerová, Z; Tesar, V (Casopis lekaru ceskych, 2001)
This is a case report of a patient with Wegener's granulomatosis (WG), who initially presented with a corneal perforation. In addition to the eye involvement, the pauciimmune necrotizing glomerulonephritis with crescent formation, E.N.T. and pulmonary involvement were diagnosed. The patient also suffered from the acute myocardial infarction, most likely due to coronal arteritis. In addition to the coronal ischaemia she also had vasculitis of the aortic valve due to the WG. Another rare complication was the massive intestinal bleeding. The patient had also a skin vasculitis and non-specific symptoms such as artralgias and fever. The correct diagnosis was supported by positive cANCA. A clinical and laboratory remission of the disease was achieved by combined immunosuppressive therapy. Subsequently, she developed a subglotic stenosis possibly due to reparative changes.
Keywords: nemoci rohovky; plicní nemoci; mužské pohlaví; infarkt myokardu; Adult; Granulomatosis with Polyangiitis; Myocardial Infarction; Gastrointestinal Hemorrhage; Lung Diseases; gastrointestinální krvácení; ženské pohlaví; Humans; Heart Valve Diseases; dospělí; Corneal Diseases; granulomatóza s polyangiitidou; nemoci srdečních chlopní; Female; lidé; Male